Pesantren’s Knowledge Identity Crisis in the Digital Era - Rosowulan, Titis; Hasyim, Ahmad Fuad; Sholikhun, Muhammad; Purwanto, Purwanto; Djamil, Abdul; In'amuzzahidin, Muh; Wijaya, Roma (Jurnal Ilmiah Peuradeun, 2025)
This article aims to examine the knowledge identity crisis faced by pesantren in Indonesia as a result of developments in the digital era. The research was conducted at three major pesantren: Futuhiyyah Mranggen, Al-Asy’ariyah Wonosobo and Al-Munawir Yogyakarta. Data were collected through participatory observation, interviews with pesantren managers, including Kiai, administrators, and teachers, as well as documentation of relevant materials. The findings reveal that the knowledge identity crisis in pesantren during the digital era manifests in several ways: an excessive learning burden on santri unrelated to the core competencies of pesantren knowledge, a decline in santri’s interest in studying traditional pesantren knowledge, and the institutional development of pesantren that has become disoriented from their foundational knowledge identity. To address this crisis, pesantren must refocus their learning programs to align with core competencies, reorient their knowledge systems to be adaptive and responsive to global needs, and restructure their institutions to remain rooted in the core knowledge identity of pesantren.